2018
DOI: 10.1002/ijc.31974
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities, age and period of diagnosis influence treatment and outcomes in early breast cancer

Abstract: Survival for breast cancer (BC) is lower in eastern than northern/central Europe, and in older than younger women. We analysed how comorbidities at diagnosis affected whether selected standard treatments (STs) were given, across Europe and over time, also assessing consequences for survival/relapse. We analysed 7581 stage I/IIA cases diagnosed in 9 European countries in 2009-2013, and 4 STs: surgery; breast-conserving surgery plus radiotherapy (BCS + RT); reconstruction after mastectomy; and prompt treatment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 31 publications
8
27
2
Order By: Relevance
“…Factors associated with treatment noncompliance. In agreement with previous studies, tumor characteristics (pre-surgical tumor size, grade, proxy subtype) and age at diagnosis were associated with initiation of recommended treatment [22][23][24] . Many factors can potentially influence a patient's decision to go along with recommended treatment: previous experiences and personal values 17 , fear of treatment-related side effects 18 , financial ability, age, education and health status, among others 19,20 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Factors associated with treatment noncompliance. In agreement with previous studies, tumor characteristics (pre-surgical tumor size, grade, proxy subtype) and age at diagnosis were associated with initiation of recommended treatment [22][23][24] . Many factors can potentially influence a patient's decision to go along with recommended treatment: previous experiences and personal values 17 , fear of treatment-related side effects 18 , financial ability, age, education and health status, among others 19,20 .…”
Section: Discussionsupporting
confidence: 91%
“…treatment in older patients 35 . Clinicians are less likely to recommend aggressive or invasive treatment such as chemotherapy or surgery for older women due to the increased likelihood of existing comorbidities 23,24 . Nonetheless, older patients can benefit from optimal anti-cancer therapy.…”
Section: Treatment Compliance and Overall Survival The High Mortalitmentioning
confidence: 99%
“…It is known that older patients or patients with comorbidities often receive non-standard treatments. A recent analysis of 7581 early stage BC patients diagnosed in 9 European countries analyzed the influence of comorbidities on receiving standard treatments and found that mastectomy was mainly given to elderly women and women with comorbidities [38]. There are several other limitations to effectiveness research due to unpredictable confounding factors and consequently, misinterpretations of treatment and mortality effects should be avoided [39].…”
Section: Discussionmentioning
confidence: 99%
“…Extended female hormone exposure by the use of hormone-replacement therapy or early menarche or late menopause also increases the risk for breast cancer [3]. Mutations in the BRCA1 and BRCA2 genes represent a predisposing factor for breast cancer [5], similarly to a family history of breast cancer or personal history of neoplastic diseases or breast cancer [3] Finally, dense breast is an independent risk factor of breast cancer [1,6]. Physical activity, successful pregnancies, and lactation are protective factors [2,3].…”
Section: Breast Cancer a Leading Cause Of Death Among Womenmentioning
confidence: 99%